2016
DOI: 10.1002/bkcs.10801
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Patterns of Three C20 Isomer Clusters: Tight‐binding Molecular Dynamics Simulation

Abstract: We investigated the decomposition pattern of three C 20 carbon isomer clusters using molecular dynamics simulations combined with the empirical tight-binding total energy calculation method. Here, the thermodynamic behaviors show up for 2 ps. Dynamic behavior is researched by considering the change in assembly energy, bond distance distribution, total energy, and potential energy as a function of temperature. The bonds start breaking around 3300, 4500, and 5100 K for cage, bowl, and ring isomers, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This potential has been successfully applied to various carbon systems . In addition, fragmentation of C 60 and C 70 clusters and C 20 isomer clusters has already been studied using these TBMD parameters …”
Section: Introductionmentioning
confidence: 99%
“…This potential has been successfully applied to various carbon systems . In addition, fragmentation of C 60 and C 70 clusters and C 20 isomer clusters has already been studied using these TBMD parameters …”
Section: Introductionmentioning
confidence: 99%
“…This potential has been successfully applied to various carbon systems [ 14 , 15 , 16 , 17 ]. In addition, the fragmentation of C 60 [ 18 ] and C 70 [ 19 ] clusters, C 20 isomer clusters [ 20 ], and C 60 @SWCNT [ 7 ], and (C 60 ) 2 @SWCNT [ 8 ] has already been studied using these TBMD parameters.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Chemical reactions by monitoring time-dependent changes in the atomic position that respond to molecules for the study of the bifurcation reaction of fullerenes inside carbon nanotubes were visualized by the high-resolution transmission electron microscopy (HR TEM) was used as a function of electron dose. [12][13][14][15] In the TBMD calculations, we use 7.08 × 10 −16 s as one-time step. Through counting reaction events one by one using HR TEM, it was proposed to convert the excited state path and thermal relaxation, the radical cation path of the C 60 dimer from the electron-damaged SWNT, and a conversion of the C 60 dimer into a fused dimer.…”
mentioning
confidence: 99%
“…Herein, carbon system parameters were obtained by means of reproducing the universal binding energy curves of the various stages obtained on the basis of calculations of the first principles. [12][13][14][15] In the TBMD calculations, we use 7.08 × 10 −16 s as one-time step. [8][9][10][11] In addition, studies using these TBMD parameters have already reported the fragmentation of C 60 and C 70 clusters, C 20 isomer clusters, and C 60 @SWNT.…”
mentioning
confidence: 99%